TNF-? as a predictive factor of pulmonary hypertension in children with Down syndrome with and without congenital heart disease - Latifah Rahmi Hariyanti; Sri Lilijanti Widjaja; Dwi Hidayah (Indonesian Pediatric Society, 2022)
Background Down syndrome (DS) is a chromosomal disorder due to trisomy 21 that may involve congenital heart disease (CHD). Pulmonary hypertension (PH) may be present in DS with and without CHD. TNF-Î± is a cytokine involved in the pathogenesis of inflammation in PH. Objective To determine the association between TNF-Î± and the risk of PH in children with DS with and without congenital heart disease. Methods This observational study was conducted in DS children aged two months to five years who visited the outpatient clinic of a regional referral hospital in Indonesia. Subjects underwent echocardiography and were classified into four groups (CHD-PH, CHD-no PH, no CHD-PH, no CHD-no PH). Serum TNF-Î± was measured in all subjects. We used the ANOVA test to compare mean TNF-Î± between the groups and to determine the optimal TNF-Î± cut-off point. We compared the risk of PH in subjects with TNF-Î± above and below the cut-off point. Results We included 36 DS children in this study. Mean TNF-Î± in the CHD-PH, CHD-no PH, no CHD-PH, and no CHD-no PH groups was 2,564.44 (SD 177.00) pg/mL, 2,112.89 (SD 382.00) pg/mL, 2,211.56 (SD 330.70) pg/mL, and 1,118.89 (SD 1056.65) pg/mL, respectively (p<0.001). The optimal TNF-Î± cut-off point was 2,318 pg/mL. DS children with TNF-Î± â‰¥2,318 pg/mL had a higher risk of CHD (RR=2.6; 95%CI 1.17 to 5.78; p=0.008) and PH (RR=3.5; 95%CI 1.43 to 8.60; p=0.001). Conclusions DS children with CHD accompanied by PH have significantly higher TNF-Î± levels than those without PH and those without CHD. In children with DS, an elevated TNF-Î± level (â‰¥2,318 pg/mL) is associated with a higher risk of CHD and PH.